3(2x+4)-10=2x+1

Simple and best practice solution for 3(2x+4)-10=2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+4)-10=2x+1 equation:


Simplifying
3(2x + 4) + -10 = 2x + 1

Reorder the terms:
3(4 + 2x) + -10 = 2x + 1
(4 * 3 + 2x * 3) + -10 = 2x + 1
(12 + 6x) + -10 = 2x + 1

Reorder the terms:
12 + -10 + 6x = 2x + 1

Combine like terms: 12 + -10 = 2
2 + 6x = 2x + 1

Reorder the terms:
2 + 6x = 1 + 2x

Solving
2 + 6x = 1 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
2 + 6x + -2x = 1 + 2x + -2x

Combine like terms: 6x + -2x = 4x
2 + 4x = 1 + 2x + -2x

Combine like terms: 2x + -2x = 0
2 + 4x = 1 + 0
2 + 4x = 1

Add '-2' to each side of the equation.
2 + -2 + 4x = 1 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = 1 + -2
4x = 1 + -2

Combine like terms: 1 + -2 = -1
4x = -1

Divide each side by '4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| X+.045=10500 | | 3x+6=10-2 | | 5(2x-4)=5+10x-9 | | 3(x-2)=3(-2+x) | | -8(-7+r)=12 | | -3a+4=-6a-17 | | 10x=14y+8 | | 36/-4*3+-8= | | 4x+2(6-5x)=-2x-4(x-1) | | 3x+4y+10=0 | | m^2=5 | | 6y-4=5+3y | | 84=7(8+x) | | 3n-5=8(6n+5) | | 4t-6-6t=6 | | 3[4/3-y]=7 | | 157=-7(4x+5)-7x | | 3x+4y+26=0 | | -5-3[15-4(-5+3)]= | | 2+4x=23-3x | | 20=4t | | 3n=12-n | | -10x-(4x-8)= | | -136=-4(-6+8n) | | 10000-k^2=9879 | | 10.50+6+2.25(2)+1d+2d=39.75 | | 4(1-3x)=-8x+4 | | 2.5(12.75x+24.50)=188.75 | | 5m^2-37m+42=0 | | 6-5=13 | | -98=-2(1+6b) | | x+3x+6x= |

Equations solver categories